DEVELOPMENT OF DISCOVERY LEARNING LEARNING MODEL WITH THINK, TALK, WRITE STRATEGY IN IMPROVING NARRATIVE TEXT WRITING SKILLS OF GRADE V STUDENTS AT UPT SDN 16 BANGKALA, JENEPONTO REGENCY - Khaeratih, Mufliha; Munirah; Rosmini (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This research aims to develop a Discovery Learning learning model with the Think, Talk, Write (TTW) strategy to improve the application of narrative text writing learning in grade V students at UPT SDN 16 Bangkala, Jeneponto Regency. This research uses a Research and Development (R&D) approach by adapting a 4D development model which includes the define, design, develop, and disseminate stages. The research instruments consisted of expert validation sheets, observations, teacher and student practicality questionnaires, and writing ability tests. The results of expert validation showed that the developed learning model was in the very feasible category, with a feasibility score of 92%. The practicality test also showed high results, namely 91% of teachers and 89% of students, which indicates that this learning model is easy to understand, easy to apply, and encourages active involvement of students in the learning process. Descriptively, the results of the pre-test and post-test illustrate a change in students' ability to write narrative texts, from an initial average score of 62.50 to 82.30 after the application of the developed learning model. Thus, this study concludes that the Discovery Learning learning model with the Think, Talk, Write strategy is feasible, practical, and has the potential to support the improvement of the writing skills of elementary school students. This model is recommended to be implemented more widely in Indonesian language learning, especially in narrative writing skills, and can be used as a reference for the development of literacy learning at the elementary education level.